Arabic Learning Strategies on Social Media: A Study of Students at Madrasah Al-Furqan Medan - Leoni Wilyam; Aura Zammiya; Liana Pertiwi; Sahkholid Nasution (Young Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the role of social media in improving Arabic language skills in students in madrasas/schools and identify its benefits and challenges. This research uses a qualitative approach with a case study method conducted at Madrasah Al-Furqan, Medan. The data was obtained through in-depth interviews of students who used social media for Arabic language learning. Data analysis was carried out using thematic analysis techniques. The findings show that social media, especially platforms such as YouTube, Instagram, and TikTok, have proven to be effective in improving Arabic language skills. Users reported improvements in vocabulary, grammar comprehension, and speaking skills. However, challenges arise related to the use of non-standard language and the lack of structure in learning. This research provides input to teachers to be innovative in fun learning so that it is more structured and collaborative between teachers and digital content creators to improve the quality of Arabic language learning on social media.